PENGARUH TINGKAT SUKU BUNGA BANK INDONESIA (BI RATE) DAN HARGA MINYAK DUNIA TERHADAP INFLASI DI INDONESIA - Agnes Theresia Dabukke; Yusni Maulida; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the effect of the interest rate of Bank Indonesia (BI Rate) and world oil prices on inflation in Indonesia during the period 2001-2015. The scope of this study conducted in Indonesia by year study period from 2001 to 2015. The data used in this research is quantitative data in the form of numbers.This study uses secondary data obtained from Bank Indonesia, the Central Bureau of Statistics and the International Energy Administration website. Data collection techniques used in this research is time series data in Indonesia. The study used multiple linear regression analysis with Ordinary Least Square method (OLS) with SPSS version 21.0. The results showed that simultaneous test (F test) showed that all independent variables were studied together have a significant effect on the dependent variable. In partial test (t test) showed variable Interest Rate Bank Indonesia (BI Rate) positive and significant effect on Inflation in Indonesia and World Oil Prices variable positive and significant effect on Inflation in Indonesia. The magnitude of the effect that (R2) by these three variables together against the dependent variable was 70.4%, while the remaining 29.6% is influenced by other variables not examined in this study.Keywords : BI Rate, World Oil and Inflation